A Comprehensive Design Guide to Adaptive e-Learning System Based on VARK Learning Styles - Anintan Savytri; Dianing Ratri (Universitas Pendidikan Indonesia (UPI), 2023)
An adaptive e-learning system is a system that caters to the needs of learners such as their learning style and knowledge. The adaptive e-learning system has been proven to improve the outcomes of learners and increase their motivation to learn. Several techniques could be used to create an adaptive e-learning system, one of them is adjusting the materials according to learners’ learning style. VARK Learning style is one of the learning styles that is fitted to be applied to adaptive e-learning systems and help learners understand how they learn better. To make an adaptive e-learning system based on VARK learning styles, there are several things to be noted. An adaptive e-learning system has three main components consisting of learner model, domain model, and adaptation model. Since the VARK learning style is flexible, it could be adjusted according to the study materials when needed by combining one style with another to create a combined style suited to the study materials. A multimodal mode is also needed to fully cater to the needs of learners who have more than one learning style. This can be done by providing them with features representing each of the main four VARK learning styles and letting the learners choose the needed features. This paper emphasizes the main foundation of an adaptive e-learning system and the needs of multimodal features in it, including a design framework to help get a better understanding of designing an adaptive e-learning system for learning applications.